Asia's economic growth and its impact on Indonesia's tigers. (March 2018) - Linkie, Matthew; Martyr, Debbie; Harihar, Abishek; Mardiah, Sofi; Hodgetts, Timothy; Risdianto, Dian; Subchaan, Moehd; Macdonald, David
Abstract: Illegal wildlife trade represents a major threat to biodiversity. Recent wildlife consumption trends across Asia have shown shifts in preference towards new species, such as Sunda pangolin, and increased volumes of consumption for longer-traded species, such as tiger. These trends are widely thought to be a result of the higher levels of wealth generated from the impressive economic growth experienced across Asia. This raises important questions regarding the role that economic growth plays as a driver of poaching on source populations of highly-prized species. As a first step to answering these, we investigate trade dynamics related to the poaching of tigers and their principal prey using a long-term biological and economic data set. The fluctuating poaching patterns recorded for tiger prey, which are locally consumed for their meat, showed no association with rising domestic beef prices, the most likely substitutable protein source. However for tiger, annual poaching rates were positively and significantly correlated with changes in local tiger skin prices that, in turn, were closely correlated with annual GDP changes in the key consumer countries. Our preliminary analysis raises further questions around the causal pathways through which rising affluence and extinction risk are linked; a question that should be posed for a wide set of species. Thus, the strong regional leadership that has enabled high economic growth across Asia and lifted hundreds of millions of people out of poverty should now be urgently directed to tackling illegal wildlife trade and, as a priority, to closing domestic and international trafficking routes. Highlights: We investigated trade dynamics related to poaching of tiger and prey over 12 years. Fluctuating prey poaching patterns were not associated with domestic beef prices. Tiger poaching was positively correlated with skin prices and consumer country GDP. Our preliminary analysis raises questions over rising affluence and extinction risk.